THE EFFECT OF USING PORPE METHOD TOWARD READING COMPREHENSION OF THE SECOND YEAR STUDENTS AT SMA N 04 BENGKULU CITY - Muhammad Faaris (Language-Edu, 2021)
Reading is a very beneficial supply of knowledge, especially for students. To produce knowledge, students ought to recognize a reading. Because studying and perception a reading is different, this research goals to determine the analyzing comprehension potential of students the use of the PORPE method or not, and whether or no longer it has an effect. There will be 5 conferences in the classroom, the first is a pre-test, the second is remedy and the ultimate is a post-test. SMA N four Bengkulu City is where this lookup took place. Researcher bought 2 instructions in conducting this research, particularly category XI IPA 3 as an experimental classification totaling 29 students, and classification XI IPA 4 as a control category totaling 29 people, a complete of 58 students. To analyze the data, the researcher used the t-test sample system the usage of SPSS 20. Before conducting the research, the researcher observed that the problem in the category to be studied was that their reading comprehension ability used to be nonetheless exceedingly weak. It can be viewed from the English rankings and analyzing tests from the type teacher data. This is due to various factors, such as the boring method taught, the students' lack of activity in studying and the lack of memorizing the vocabulary they know. In this case, the PORPE technique is expected to be the solution. The objectivity of this research is 1. To determine whether there is an effect of the use of the PORPE approach on analyzing capabilities in eleventh grade students of SMA N four Bengkulu City. two To find out whether or not there is a huge distinction between the studying comprehension of students taught with the PORPE method and those taught except the PORPE method. After examining the data, the researcher concluded that there used to be a substantial impact of the usage of the PORPE approach on studying comprehension of students of SMAN four Bengkulu which was based on statistical calculations, the importance price of t was 0 much less than 0.05. So it can be concluded that there is a difference in the average scholar studying effects between the PORPE gaining knowledge of model and the traditional model. Based on these results, it can be concluded that the Zero Hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted.Keywords: Reading Comprehension, PORPE Method